EXPLORING THE POTENTIAL OF HUMIC SUBSTANCES AS EFFECTIVE SORBENTS FOR REDUCING GREENHOUSE GAS EMISSIONS (Eurasian Journal of Ecology, 2023)
This article explores the potential of humic substances, which are naturally occurring organic compounds found in soil, water, and coal, as a solution for reducing greenhouse gas emissions. The study specifically examines the humic substances extracted from the Maikube brown coal basin. The properties and mechanisms of humic substances that make them effective in mitigating greenhouse gas emissions are discussed, with early research results on the absorption processes of potassium humate provided. The article also reviews current research on the use of humic substances for carbon capture and storage and highlights the potential for scaling up this technology as a low-cost and efficient approach to reducing greenhouse gas emissions. The concentration of CO2 was measured at the inlet and outlet of the gas in a gas chromatograph. Within 4 days, the absorption capacity of potassium humate (50%) was 4.99 g CO2/kg. The IR spectrum of potassium humate is presented as well. The article concludes that while humic substances have the potential to be a promising solution for reducing greenhouse gas emissions, further research and development are required to determine their full potential.Keywords: greenhouse gases, humic substances, absorption, CO2 capture, potassium humate.